The significance of masticatory muscle’s relaxation in the treatment of the temporomandibular disorders — Review article - Pihut, Małgorzata; Orczykowska, Magdalena; Ceranowicz, Piotr; Korzonek, Ilona; Gala, Andrzej (Folia Medica Cracoviensia, 2023)
Temporomandibular disorder (TMD) is a disease of multifactorial etiology and a complex of symptoms, related to disorders of the masticatory muscles, temporomandibular joints and the surround-ing orofacial structures. One of the main problems in the course of TMD disorders is the systematic increase in the tension of the masticatory muscles (masseter muscles, temporalis and medial and lateral pterygoid muscles), what is the cause of many damages and the development of pathological conditions in the stomatognathic system. The article discusses the differences in the structure of the masticatory and skeletal muscles, as well as the different nature and isoforms of myosin, which determines the much faster generation of contraction in the masticatory muscles and consequently easier generation of excessive, harmful tensions in the masti-catory muscles. The article describes the causes of increased tension in the masticatory muscles and methods of their relaxation used in the basic and supportive treatment of temporomandibular disorders. The use of occlusal splints, physiotherapeutic procedures and TMD treatment with botulinum toxin type A were character-ized. A role of psychological support and the methods used for patients with TMD were emphasized.
Keywords: temporomandibular disorder; TMD; relaxation of the masticatory muscles; botulinum toxin injection; physiotherapy; manual therapy; exercise of masticatory muscles; allotypes; myosin